The River Eco-Lexicons in the Texts of Riau Malay - Mohd Fauzi; Denni Iskandar (Proceedings of AICS - Social Sciences, 2021)
Riau has many eco-lexicons related to rivers and their environment. This language phenomena is urgent to be researched, revealed and documented.This study is aimed to reveal the form and category of eco-lexicons found in the texts of Riau Malay. This research used critical ecolinguistics. Data were collected by applying observation and note-taking techniques. Descriptive qualitative method was used to analyze the objective of the research. The results showed that there were many eco-lexicons of river environments found in the three folklores namely Ulak Patian dan Toi Burong Kwayang, Hikayat Kepenuhan, and Tuanku Datuk Panglima Nyarang. These eco-lexicons are revealed in the texts through their conversation and interaction. The river eco-lexicons found are in the form of basic words and some are affixed to the categories of nouns, verbs, and adjectives. The existence of eco-lexicons related to rivers showed that the Bonai community depended on nature, especially the river and its environment. Importantly, their activities in managing their nature were local wisdom that existed for generations.Keywords: Eco-Lexicons, Malay Texts, Folklore, Eco-Linguistics